Antimicrobial Activity and LC Determination of Ethanol Crude Extract of 50 Pliek U, an Achehnese Traditional Fermented Food - Nurliana Nurliana; Mirnawati Sudarwanto; Lisdar I. Sudirman; Angelina W. Sanjaya (Universitas Syiah Kuala, 2010)
Antimicrobial activity of pliek u crude extracts was evaluated against five bacterial species (Staphylococcus aureus, Bacillus cereus, Escherichia coli, Salmonella enterica serovar Enteritidis and Pseudomonas aeruginosa,)and one fungal species (Candida albicans). Pliek u has been consumed as spices and hot sauce and poultry feed. These foods were collected from household industry at Reudep village in Aceh Besar, Province of Aceh. The ethanol extract of pliek u were obtained by standard method. The antimicrobial activity was detected using paper disc method. The concentration of ethanol crude extract of pliek u (EEP) was determined with the dilution method. The lethality initial test has been detected by using Artemia salina L. bioassay to determine the toxic concentration based on the LC value of EEP. The ethanol crude extract (EEP) was active against all microbial strains. EEP showed 50 antimicrobial activity at a minimum inhibitory concentration (MIC) and a minimum microbicidal concentration (MMC) at 2.5-10 mg/ml and 10-20 mg/ml, respectively. The lethality concentration EEP gave the LC value of 3.36 50 mg/ml. It was concluded that ethanol crude extract (EEP) shows significant antimicrobial activity and it is not toxic.